Comparative transcriptome analysis reveals genetic diversity in the endosymbiont Hamiltonella between native and exotic populations of Bemisia tabaci from Brazil - De Marchi, Bruno Rossitto [UNESP]; Kinene, Tonny; Wainaina, James Mbora; Krause-Sakate, Renate [UNESP]; Boykin, Laura (Public Library of Science (PLoS), 2018)
The whitefly, Bemisia tabaci, is a species complex of more than 40 cryptic species and a major agricultural pest. It causes extensive damage to plants mainly by transmitting plant viruses. There is still a lack of genomic data available for the different whitefly species found in Brazil and their bacterial endosymbionts. Understanding the genetic and transcriptomic composition of these insect pests, the viruses they transmit and the microbiota is crucial to sustainable solutions for farmers to control whiteflies. Illumina RNA-Seq was used to obtain the transcriptome of individual whiteflies from 10 different populations from Brazil including Middle East-Asia Minor 1 (MEAM1), Mediterranean (MED) and New World 2 (NW2). Raw reads were assembled using CLC Genomics Workbench and subsequently mapped to reference genomes. We obtained whitefly complete mitochondrial genomes and draft genomes from the facultative bacterial endosymbiont Hamiltonella for further phylogenetic analyses. In addition, nucleotide sequences of the GroEL chaperonin gene from Hamiltonella from different populations were obtained and analysed. There was concordance in the species clustering using the whitefly complete mitogenome and the mtCOI gene tree. On the other hand, the phylogenetic analysis using the 12 ORF’s of Hamiltonella clustered the native species NW2 apart from the exotics MEAM1 and MED. In addition, the amino acid analysis of GroEL chaperonin revealed a deletion only in Hamiltonella infecting NW2 among whiteflies populations analysed which was further confirmed by PCR and Sanger sequencing. The genomic data obtained in this study will aid understanding the functions that Hamiltonella may have in whitefly biology and serve as a reference for further studies regarding whiteflies in Brazil.